2021
DOI: 10.1186/s13104-021-05566-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task difficulty during practice on learning a dynamic balance task in healthy young adults: An intervention study

Abstract: Objective Cross-sectional studies reported increased postural sway during balance tasks with a high (e.g., unipedal stance on foam ground) compared to a low (e.g., unipedal stance on firm ground) level of task difficulty. Therefore, practicing/training balance tasks using high compared to low stimuli seems to be beneficial as it addresses larger adaptive reserves. Thus, the present study was performed to investigate the role of task difficulty during practice on learning a dynamic balance task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…There is no doubt that task repetition leads to improved stance control, for example, assessed behaviourally, where the "time in balance" increases with short-term training (Schedler et al, 2021). Getting closer to the underpinning mechanisms, we suggest that, when subjects stand on foam, the brain soon realises that minimisation of the body displacement per se is not an efficient way of coping with the critical condition (Kiemel et al, 2011).…”
Section: The Function Of the Adaptationmentioning
confidence: 81%
See 1 more Smart Citation
“…There is no doubt that task repetition leads to improved stance control, for example, assessed behaviourally, where the "time in balance" increases with short-term training (Schedler et al, 2021). Getting closer to the underpinning mechanisms, we suggest that, when subjects stand on foam, the brain soon realises that minimisation of the body displacement per se is not an efficient way of coping with the critical condition (Kiemel et al, 2011).…”
Section: The Function Of the Adaptationmentioning
confidence: 81%
“…This epoch was not further divided into time segments and formally analysed to see if an adaptation occurs between the first and last part of the same trial. A related unanswered issue is the duration and amplitude of the adapted effects and the capacity to exploit learning for coping with difficult tasks (Schedler et al, 2021). In other words, we do not know whether and how post-effects of adaptation in sway or spectral measures fade over time.…”
Section: Limitationsmentioning
confidence: 99%
“…A limit of the present study was that the ability to maintain a challenging posture such as the unipedal stance was investigated only soon after the training session. It has been shown that the effects of a single session in postural training may persist the whole day, so that they may sum to those of another training session performed the day after [70]. This is probably the reason why repeated session of postural training regularly spaced within the week may lead in the long term to substantial improvements of postural stability [1,[5][6][7][8][9][10][11][12][13][14].…”
Section: Persistence Of Postural Learning and Translational Applicationsmentioning
confidence: 99%